Existence and uniqueness for some nonlocal elliptic problem. Issue 15 (18th November 2018) - Liang, Fei; Qiao, Huan
Abstract: In this paper, we consider the existence and uniqueness of solutions for the nonlocal elliptic problem with homogeneous Dirichlet boundary conditions, where, . It will be shown that: (i) when, there exists a unique solution to the nonlocal elliptic problem for any ; (ii) when, there also exists a unique solution of the nonlocal elliptic problem for and no solution for .